Evolution of a taboo pigs and people in the Ancient Near East - Price, Max D. ca. 20./21. Jh. (New York, NY Oxford University Press, 2020)
From their domestication to their taboo, pigs and their shifting roles in the ancient Near East are among the most complicated topics in archaeology. Rejecting monocausal explanations, this text adopts an evolutionary approach and draws upon zooarchaeology and ancient texts to unravel the cultural significance of swine from the Paleolithic to today.
Also issued in print: 2021. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on November 19, 2020)
Keywords: Swine -- History -- To 1500 -- Middle East; Animals -- Social aspects -- History -- To 1500 -- Middle East; Swine -- Religious aspects -- Judaism; Swine -- Religious aspects -- Islam; Taboo -- Middle East; Mammal remains (Archaeology) -- Middle East; Swine ; Middle East ; History ; To 1500; Animals ; Social aspects ; Middle East ; History ; To 1500; Swine ; Religious aspects ; Judaism; Swine ; Religious aspects ; Islam; Taboo ; Middle East; Mammal remains (Archaeology) ; Middle East; Middle East ; Antiquities; Middle East -- Antiquities